Experiences regarding exclusive breastfeeding practice among ethnic minority mothers in rural areas of Bokeo province, Lao PDR - Kapheak, Krissana; Theerawasttanasiri, Nonthaphat; Khumphoo, Potchara; Chayaseng, Chansy; Bounmaseng, Phouangphet; Pangsri, Ninrat; Kaewsingsu, Kanlayanee; Wungrath, Jukkrit (Science, Engineering and Health Studies, 2025)
This qualitative study explores exclusive breastfeeding practices among ethnic minority mothers in Bokeo province, Lao PDR. Utilizing purposive sampling, the research engaged 36 ethnic mothers from five different villages, identified with the help of local health volunteers. This method ensured a diverse group of participants, representing various ethnic backgrounds, age groups, parity levels, and socioeconomic statuses within this marginalized region. The study investigates the intricate interplay between cultural traditions, socioeconomic challenges, and limited healthcare access that shape breastfeeding practices. Through in-depth interviews with these ethnic mothers, it unveils their unique experiences and decision-making processes regarding breastfeeding. Key findings highlight the influence of traditional beliefs such as colostrum avoidance and complementary feeding, alongside economic pressures that compel mothers to resume work soon after childbirth. Additionally, the limited access to healthcare information and support emerged as a significant barrier to exclusive breastfeeding. The study emphasizes the need for culturally sensitive health interventions, enhanced community engagement, and supportive policies tailored to the specific needs of breastfeeding mothers in ethnically diverse, rural areas. Addressing this issue should involve a variety of measures, particularly community engagement. Involving community leaders or experienced members who have practiced breastfeeding can enhance cooperation from nursing mothers significantly.